Expressions of National Crisis: Diamela Eltit's E. Luminata and Pablo Picasso's Guernica - Gisela Norat (Studies in 20th & 21st Century Literature, 2006)
Diamela Eltit emerged as a writer during the 1980s when Chile was ruled by the military dictatorship of General Augusto Pinochet (1973 -1989). The obscurity of her first book, Lumpérica (trans. E. Luminata) reflects that period of national repression. Despite the negligible attention she received for her first novel, Eltit has since published six other novels and managed to carve out a place for herself within Chile's predominantly male literary establishment. Her writing challenges its mainstream cultural apparatus with a female-centered postmodern writing very different from that of compatriots like best selling authors Isabel Allende in the United States and Marcela Serrano in Chile. Given the symbolic elements of Eltit's text and the difficulty it poses for readers, I propose using Pablo Picasso's widely known Guernica as a visual aid in understanding the fragmented and abstract nature of Eltit's first novel, a text that the reader should not expect to understand entirely. This study draws historical and artistic parallels with Picasso's well-known mural, a painting that has come to symbolize an anti-war cry in its depiction of man's inhumanity to man, woman, and child—a recurrent theme in Eltit's writing.
Keywords: Diamela Eltit; Chilean; Chile; Pinochet; Lumpérica; E. Luminata; national repression; female; male; female literature; Picasso; Cuernica; abstract; fragmentation